The Improvement of Writing Teaching for English Major and the Intervention of Culture in Chinese Universities - Dan, Liu (Cultural and religious studies, 2022)
The new era context puts forward new requirements for the writing teaching for English majors in Chinese universities, and the intervention of culture has become a necessary content of writing teaching. Combined with the shortcomings of English writing teaching in universities in China, based on the analysis of the positive significance of cultural intervention in writing teaching, this paper focuses on the basic strategies of cultural intervention, that is, to clarify the cultural implication behind the complicated English vocabulary; collect relevant cultural materials according to the teaching content of writing class; for the idioms often used in writing, compare the cultural differences between China and the West. Cultural intervention contributes to the improvement of writing teaching, but it could not become the main content of writing teaching. Mastering the writing methods and skills of various styles is still the main goal of writing teaching.